The literature review : a step-by-step guide for students - Ridley, Diana (Los Angeles, CA. : SAGE, 2012)
This title is a concise, step-by-step guide to conducting a literature search and writing up the literature review chapter in a master dissertation or a professional doctorate thesis.
Includes bibliographical references and index.
Specialized.
Keywords: Research; Research -- Evaluation; Academic writing; Report writing